Nikon D5000 digital field guide - Thomas, J. Dennis (Wiley Pub., 2009)
"Whether you're new to dSLR photography or moving up from a less feature-rich camera, you'll learn to use all the controls of your D5000 and how to get perfect shots in all types of situations. The Quick Tour gets you started, and the step-by-step instructions give you confidence to move from the Auto function into full manual control"--Resource description page.